William H. Moody papers - Moody, William H. (William Henry), 1853-1917.
Correspondence and miscellany. Correspondents include James Burrill Angell, Ray Stannard Baker, Gist Blair, Jules Boeufve, Joseph Gurney Cannon, Benjamin Chester Chapin, Moses E. Clapp, Waldo Lincoln Cook, George B. Cortelyou, William Crozier, Charles Dick, Charles William Eliot, Stephen B. Elkins, Franklin G. Fessenden, Addison G. Foster, Augustus Peabody Gardner, James Gibbons, Frederick Huntington Gillett, Daniel Coit Gilman, Eugene Hale, John Hay, Hilary A. Herbert, Robert Cochran Hilliard, Julius Kahn, John Kean, William W. Kitchin, Philander C. Knox, Thomas Barton Kyle, Henry Cabot Lodge, William Loeb, John Davis Long, Francis C. Lowell, Wayne MacVeagh, J.T. McCleary, John James McCook, Joseph Robinson. McCready, Porter J. McCumber, Henry McManus, Thomas C. McRae, William D. Meany, Victor Howard Metcalf, George von Lengerke Meyer, Boies Penrose, Charles Henry Robb, Theodore Roosevelt, Elihu Root, Edward Rosewater, Henry L. Stimson, William H. Taft, Richard W. Thompson, and Booker T. Washington.
U.S. Supreme Court justice, attorney general, secretary of the navy, and representative from Massachusetts.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Angell, James Burrill, -- 1829-1916 -- Correspondence; Baker, Ray Stannard, -- 1870-1946 -- Correspondence; Blair, Gist, -- 1860-1940 -- Correspondence; Boeufve, Jules -- Correspondence; Cannon, Joseph Gurney, -- 1836-1926 -- Correspondence; Chapin, Benjamin Chester, -- 1874-1918 -- Correspondence; Clapp, Moses E. -- 1851-1929 -- Correspondence; Cook, Waldo Lincoln, -- 1865-1951 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Crozier, William, -- 1855-1942 -- Correspondence; Dick, Charles, -- 1858-1945 -- Correspondence; Eliot, Charles William, -- 1834-1926 -- Correspondence; Elkins, Stephen B. -- 1841-1911 -- Correspondence; Fessenden, Franklin G. -- 1849-1931 -- Correspondence; Foster, Addison G. -- 1837-1917 -- Correspondence; Gardner, Augustus Peabody, -- 1865-1918 -- Correspondence; Gibbons, James, -- 1834-1921 -- Correspondence; Gillett, Frederick Huntington, -- 1851-1935 -- Correspondence; Gilman, Daniel Coit, -- 1831-1908 -- Correspondence; Hale, Eugene, -- 1836-1918 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Herbert, Hilary A. -- 1834-1919 -- Correspondence; Hilliard, Robert Cochran, -- 1857-1927 -- Correspondence; Kahn, Julius, -- 1861-1924 -- Correspondence; Kean, John, -- 1852-1914 -- Correspondence; Kitchin, William W. -- 1866-1924 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; Kyle, Thomas Barton, -- 1856-1915 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Loeb, William, -- 1866-1937 -- Correspondence; Long, John Davis, -- 1838-1915 -- Correspondence; Lowell, Francis C. -- 1855-1911 -- Correspondence; MacVeagh, Wayne, -- 1833-1917 -- Correspondence; McCleary, J. T. -- 1853- -- Correspondence; McCook, John James, -- 1843-1927 -- Correspondence; McCready, Joseph Robinson -- Correspondence; McCumber, Porter J. -- 1856-1933 -- Correspondence; McManus, Henry -- Correspondence; McRae, Thomas C. -- 1851-1929 -- Correspondence; Meany, William D. -- Correspondence; Metcalf, Victor Howard, -- 1853-1936 -- Correspondence; Meyer, George von Lengerke, -- 1858-1918 -- Correspondence; Penrose, Boies, -- 1860-1921 -- Correspondence; Robb, Charles Henry, -- 1867-1939 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Rosewater, Edward, -- 1841-1906 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Thompson, Richard W. -- 1809-1900 -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; United States. -- Supreme Court; Cabinet officers; Jurists; Representatives, U.S. Congress -- Massachusetts